Hybrid control of a motion of an unmanned aerial vehicle, carrying an inverted pendulum - Shahinyan, A. S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The control problem of the movement of an unmanned aerial vehicle (UAV) carrying an inverted pendulum is considered. The interconnected dynamics of an unmanned aerial vehicle and an inverted pendulum are described. To solve the control mathematical linearized problem on the basis of virtual modeling of the system, a new one was applied: a hybrid method of the system control. The linearized system control problem is solved. The control actions on the system, as well as phase trajectories of the components of the system are given in the form of graphs of functions. Рассматривается проблема управления движением беспилотного летательного аппарата (БПЛА), несущего перевернутый маятник. Описана взаимосвязанная динамика беспилотного летательного аппарата и перевернутого маятника. Для решения, линеаризованной на основе виртуального моделирования системы математической задачи управления, применен новый: гибридный метод управления системой. Решена линеаризованная задача управления системой. Управляющие воздействия на систему, а также фазовые траектории движения составляющих системы приведены в виде графиков функций. Դիտարկվում է շրջված ճոճանակ կրող, քառաթև անօդաչու թռչող սարքի շարժման ղեկավարման խնդիրը: Նկարագրված է անօդաչու թռչող սարքի և ճոճանակի փոխկապակցված դինամիկան: Շարժման ընդհանուր հավասարումների գծային մոտավորության համար կիրառված է համակարգի շարժման ղեկավարման նոր՝ հիբրիդային եղանակ: Լուծված է համակարգի ղեկավարման խնդիրը: Ստացված են ղեկավարող ազդեցությունները և շարժման ֆազային հետագծերը: Կառուցված են դրանց գրաֆիկները:
Keywords: Mechanics